My Sister's Keeper - Picoult, Jodi, 1966- and Wasel, Ulrike, 1955-; Klaus Timmermann1955- (London Hodder Paperbacks, 2009)
The Richard & Judy bestseller is now a major motion picture directed by Nick Cassavetes and starring Cameron Diaz and Abigail Breslin.
A Novel, Originally published: London: Hodder & Stoughton, 2004.
Keywords: Sisters -- Leukemia--Patients -- Sick Children